The statistician : journal of the Institute of Statisticians. - Institute of Statisticians (London [England] : The Institute, 1962)
Includes proceedings of the I.O.S. Annual Conference, 1978-<1983>.
Some issues also have a theme title.
Subtitle varies.
Vol. 19 is irregular: no. 1-2 issued in 1969; no. 3-4 in 1970.
Also issued in print.
Mode of access: World Wide Web.
Official publication of: Institute of Statisticians.
Keywords: Statistics -- Periodicals; Statistique -- P eriodiques; Statistics; Statistics -- Periodicals; Periodicals; Electronic journals